The correlation between passive smoke exposure and childhood dental caries: evidence from recent studies - Gumilar, Mira Sri; Boy, Hendry (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: Dental caries in children is a global health issue, particularly in lower-income countries. Exposure to tobacco smoke is one of the major risk factors. In Indonesia, where smoking is prevalent, children exposed to passive smoke face a higher risk of dental caries. Method: A systematic review was conducted, focusing on studies published between 2019 and 2024. Literature was selected using specific keywords, with cross-sectional studies emphasizing the correlation between passive smoking and dental caries in children. Results: Of the 11 selected studies, 9 demonstrated a significant correlation between passive smoking and dental caries, with P-values below 0.05. However, the two studies showed no significant relationship, potentially due to small sample sizes or other external factors like diet or hygiene. Conclusion: Exposure to cigarette smoke significantly increases the risk of dental caries in children, necessitating public health interventions to reduce exposure and prevent oral health problems.